2014
DOI: 10.1371/journal.pone.0109061
|View full text |Cite
|
Sign up to set email alerts
|

Selective Microbial Genomic DNA Isolation Using Restriction Endonucleases

Abstract: To improve the metagenomic analysis of complex microbiomes, we have repurposed restriction endonucleases as methyl specific DNA binding proteins. As an example, we use DpnI immobilized on magnetic beads. The ten minute extraction technique allows specific binding of genomes containing the DpnI Gm6ATC motif common in the genomic DNA of many bacteria including γ-proteobacteria. Using synthetic genome mixtures, we demonstrate 80% recovery of Escherichia coli genomic DNA even when only femtogram quantities are spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…Additionally, previous studies using the MolYsis kit focused on improving techniques such as real-time PCR, whereas use of these methods for WGS, where microbial DNA enrichment could be even more useful, has been less studied (Votintseva et al, 2015). Other methods such as host cell lysis with detergents (Hasan et al, 2016) or ox bile (Zhou & Pollard, 2012) and immunoprecipitation of DNA with inactive methyl-specific restriction endonucleases (Barnes et al, 2014; Liu et al, 2016) have also been reported, but are not available as commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies using the MolYsis kit focused on improving techniques such as real-time PCR, whereas use of these methods for WGS, where microbial DNA enrichment could be even more useful, has been less studied (Votintseva et al, 2015). Other methods such as host cell lysis with detergents (Hasan et al, 2016) or ox bile (Zhou & Pollard, 2012) and immunoprecipitation of DNA with inactive methyl-specific restriction endonucleases (Barnes et al, 2014; Liu et al, 2016) have also been reported, but are not available as commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…coli genomic DNA into low molecular weight fragments (<500 bp) and showed little activity on human DNA ( S1 Fig ). To develop a magnetic bead based enrichment workflow, we removed magnesium ions from the reaction buffer which prevents digestion activity [ 12 ] but still enables HpaII to bind target DNA ( Fig 1A ). HpaII mediated enrichment conditions were optimized using selective qPCR assays on a predefined DNA mixture of Yersenia pestis and human genomes.…”
Section: Resultsmentioning
confidence: 99%
“…A volume of 0.5 ml ethanol was added and the solution was loaded on the spin column up to three times. DNA was eluted twice with 30 μl 1X Binding Buffer [ 12 ] at 60°C and the eluates were combined. The DNA yield was determined with the Qubit BR assay (LifeTechnologies).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations